The Effects Of Structured Warrants On Firm Performance In Malaysia: The Role Of Institutional Ownership - Yip, Yen Yen (2017)
This research is motivated to explore whether the existence of structured warrants creates any value to its underlying firms in both short-run and long-run based on the Malaysian structured warrants market. The time frame of this study covers year 2006 until 2014. In order to gauge the short-run impact, the analysis concerning the impact of structured warrants listing on the behaviour of its underlying stocks is performed based on the event study and dummy variable methodology. The findings reveal that the return of the underlying stocks has increased significantly surrounding the event of structured warrants listing, however, no abnormal return is being detected.